Pengaruh Electronic Word Of Mouth, Brand Imge Dan Loyalitas Pelanggan Terhadap Minat Beli Ulang Produk Skincare Skintific. (Studi Pada Mahasiswa Universitas Islam Malang Dengan Fokus Pengguna Skintific) - Febriansyah, Aldhi; Alrasyid, Harun; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), Brand Image, and Customer Loyalty on the Repurchase Intention of Skintific skincare products. The research is motivated by the increasing skincare usage among students and Skintific's strong presence in Indonesia's e-commerce market. A quantitative approach was employed by distributing questionnaires to 105 students of the Islamic University of Malang who had used Skintific products. Data were analyzed using multiple linear regression. The findings show that Electronic Word of Mouth, Brand Image, and Customer Loyalty each have a positive and significant effect on Repurchase Intention. These results suggest that positive consumer perceptions of online reviews, brand image, and loyalty directly influence their intention to repurchase. This study contributes to the development of digital marketing strategies in the beauty industry, particularly in maintaining young and digitally engaged consumers. Keywords: Electronic Word of Mouth, Brand Image, Customer Loyalty, Repurchase Intention, Skintific.